Strengths and weaknesses of the LOMLOE curricular proposal. Proyecto Atlántida - Luengo Horcajo, Florencio; Hernández-Ortega, José; Clavijo Ruiz, Manuel; Gómez Alfonso, José Antonio (Avances en Supervisión Educativa, 2021)
The Atlantis discourse repeatedly tries to facilitate meeting places in education, and this is the approach presented in the article on the LOMLOE curriculum. It is about presenting a balanced reflection on the new attempt to improve the educational model in our country, in this case on the curriculum of our education. The document also announces the positive assessment of certain educational novelties of the model proposed by the MEFP, in this case endorsed by successful educational systems in our environment, to accompany the approach with a brief description of the strengths that can be built from of the proposed model, as well as the weaknesses that the elaboration process begins to make evident. At the end of it, as an annex, several examples are described, which Atlántida, together with other innovation groups of the network for educational dialogue (REDE) have sent to the Ministry in their new curricular commitment. As is usual in Atlántida proposals, balanced reflection is the fundamental objective of the work.